EFFECT OF COLOR IN HUMAN LIFE - Sharma, Sunny (International Journal of Research -GRANTHAALAYAH, 2014)
Take a minute and imagine the world around you without colors, how boring and unexciting life would be colors play a vital role in our daily lives and if has been proven that our actives and response and influenced by them. Every color has a unique effect on individuals and stimulates various responses e.g. a research has proven that blue color enhances creativity whereas the colors red helps to be focused and has appositive effect on memory. Dark green color has a motivational effect on males. The color is yellow helps to release a chemicals in the brain called serotonin essentials for causing a happy mood and change are the happiest color. So every color different effect in our life each color corresponds with a vibrations with an every with an element and with a desired out come .getting the colors wrong can at best Make a spell fair and at work could backfires on the spell caster or recipient of the spell manifestation